Implementing a Central IRB Model in a Multicenter Research Network. Issue 3 (20th May 2019) - Burr, Jeri S.; Johnson, Ann R.; Vasenina, Valeriya; Bisping, Stephanie; Coleman, R. Whitney; Botkin, Jeffrey R.; Dean, J. Michael
ABSTRACT: Implementing the National Institutes of Health's (NIH's) new single institutional review board (IRB) policy has caused a paradigm shift in IRB review across the country. IRBs and human research protection programs are looking more closely at their processes for ceding review and developing procedures to handle local review when relying on a single IRB. This article describes an NIH‐funded network that proactively instituted a central IRB (CIRB) in 2012, anticipating the NIH future mandate. Lessons learned are described. There was a steep learning curve for IRBs and participating sites. IRB submission workload burden shifted from study teams to the data coordinating center, which created new workflow challenges, especially preparing hundreds of consent documents centrally. Despite difficulties encountered with CIRB review, this network is now fully functioning under a CIRB model. Further review and experience are needed to determine whether this shift in IRB review has eliminated duplicative review or regulatory burden from study teams.